2'-Alkynyl spin-labelling is a minimally perturbing tool for DNA structural analysis - Hardwick, Jack S.; Haugland, Marius M.; El-Sagheer, Afaf H.; Ptchelkine, Denis; Beierlein, Frank; Lane, Andrew N.; Brown, Tom; Lovett, Janet E.; Anderson, Edward A. (Nucleic Acids Research, 2020)
The determination of distances between specific points in nucleic acids is essential to understanding their behaviour at the molecular level. The ability to measure distances of 2-10 nm is particularly important: deformations arising from protein binding commonly fall within this range, but the reliable measurement of such distances for a conformational ensemble remains a significant challenge. Using several techniques, we show that electron paramagnetic resonance (EPR) spectroscopy of oligonucleotides spin-labelled with triazole-appended nitroxides at the 2' position offers a robust and minimally perturbing tool for obtaining such measurements. For two nitroxides, we present results from EPR spectroscopy, X-ray crystal structures of B-form spin-labelled DNA duplexes, molecular dynamics simulations and nuclear magnetic resonance spectroscopy. These four methods are mutually supportive, and pinpoint the locations of the spin labels on the duplexes. In doing so, this work establishes 2'-alkynyl nitroxide spin-labelling as a minimally perturbing method for probing DNA conformation.
CRIS-Team Scopus Importer:2020-04-07